HUBUNGAN INDEKS MASSA TUBUH DAN GANGGUAN PENGLIHATAN DENGAN RISIKO JATUH PADA LANSIA - Elfrida, Ribka; Erda, Roza; Gemini, Savitri (Ensiklopedia of Journal, 2025)
This study investigates the relationship between Body Mass Index (BMI) and visual impairment with the risk of falls among elderly individuals in the working area of Tiban Baru Public Health Center, Batam City, in 2024. The aging process leads to physical decline, including musculoskeletal and visual impairments, which significantly increase the risk of falls. Falls among elderly individuals are multifactorial, involving intrinsic factors such as health conditions and extrinsic factors like environmental hazards. This research employs a quantitative analytical approach to identify BMI levels, visual impairments, and fall risks among elderly residents. Findings are expected to contribute to gerontological nursing practices by highlighting the importance of maintaining normal BMI and addressing visual impairments to reduce fall risks. The study aims to provide theoretical insights and practical applications for healthcare professionals and institutions.Keywords: Elderly; Body Mass Index (BMI); Visual Impairment; Fall Risk; Gerontological Nursing; Public Health.